Uji Aktivitas Antibakteri Sediaan Obat Kumur Infusa Daun Salam (Syzygium polyanthum W.) terhadap Streptococcus mutans - Adelia Setyaningrum Permatasari; Dyah Susilowati; Susi Endrawati (Indonesian Journal on Medical Science, 2022)
Bay leaves (Syzygium polyanthan W.) contains substances of color, tanning substances and essential oils which are antibacterial. The objectives of the study were 1) to find out that the bay leaf infusion mouthwash had activity against Streptococcus mutans bacteria, This study used the well diffusion method with a diameter of 9mm. The concentrations used were 10%, 20% and 30%, positive control (Amoxicillin) and negative control (mouthwash without bay leaf infusion). The results showed that the positive control got large results with an average diameter of 19.16 mm, there was no inhibition zone in the negative control. Bay leaf infusion has activity against Streptococcus mutans bacteria at a concentration of 10% with a diameter of 10.66 mm, a concentration of 20% with a diameter of 12.33 mm, a concentration of 40% with a diameter of 15 mm. Bay leaf infusion mouthwash has activity against Streptococcus mutas with the diameter of the zone of inhibition of the bay leaf infusion mouthwash at a concentration of 10% is 10.66 mm, a concentration of 20% with diameter 12.33 mm, concentration 40% with diameter 15 mm.